The hitchhiker's guide to the galaxy - Adams, Douglas, 1952-2001. (New York : Ballantine Books, 1995)
Seconds before Earth is demolished to make room for a galactic freeway, an earthman is saved by his friend. Together they journey through the galaxy.
Wilson's Fiction.
Wilson's Junior High School.
Wilson's Senior High School.
Booklist, April 2006.
Library Journal, April 2006.
Notable/Best Books (A.L.A.), August 2006.
Keywords: Dent, Arthur (Fictitious character) -- Fiction; Prefect, Ford (Fictitious character) -- Fiction; Voyages, Imaginary; Dent, Arthur (Fictional character) -- Fiction; Imaginary voyages; Prefect, Ford (Fictional character) -- Fiction; Science fiction